The origins of acrylates and adhesive technologies in dentistry - Staehle, Hans Jörg; Sekundo, Caroline (The journal of adhesive dentistry, 2021)
PURPOSE: To examine the origins of acrylates and adhesive dentistry up to 1955. - MATERIALS AND METHODS: A search of MEDLINE database and a manual literature search were conducted to find relevant articles. - RESULTS: Acrylic acid was discovered in 1843, methacrylic acid in 1865. In 1880, light polymerization of acrylate compounds using glass prisms was introduced. In 1928, polymethyl methacrylate (PMMA) was industrially produced from methyl methacrylate (MMA). In 1930, PMMA moldings that could be adapted under heat and pressure were introduced into dentistry. The process was improved in 1936 by mixing pulverized PMMA and liquid MMA. In 1940, the intraoral polymerization of dental resins using UV light or catalysts was discovered. In the same year, the combined procedure (dual-curing) and addition of inorganic fillers to improve the material properties (precursors of composites) were proposed. Effects on the oxygen inhibition layer and intraoral bonding between several resin portions were also described. In 1942, direct restorations with self-curing resins (combined with a precursory version of cavity sealing) were described. These new resins were marketed in the late 1940s. Intraoral repair of restorations and cementation of crowns and bridges with resins were also described in 1942. In 1949, a glycerophosphoric acid-based sealer was marketed. In the same year, it was discovered that etching of the enamel (with nitric acid) caused an adhesion to thin layers of acrylic-based materials. In 1955, phosphoric acid etching of enamel was shown to improve adhesion. - CONCLUSION: In the first half of the 20th century, important but little or unknown discoveries took place. These discoveries can improve our understanding of how adhesive dentistry evolved.
Gesehen am 08.02.2022